2020
DOI: 10.1371/journal.pone.0230366
|View full text |Cite
|
Sign up to set email alerts
|

C8J_1298, a bifunctional thiol oxidoreductase of Campylobacter jejuni, affects Dsb (disulfide bond) network functioning

Abstract: Posttranslational generation of disulfide bonds catalyzed by bacterial Dsb (disulfide bond) enzymes is essential for the oxidative folding of many proteins. Although we now have a good understanding of the Escherichia coli disulfide bond formation system, there are significant gaps in our knowledge concerning the Dsb systems of other bacteria, including Campylobacter jejuni, a food-borne, zoonotic pathogen. We attempted to gain a more complete understanding of the process by thorough analysis of C8J_1298 funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 103 publications
(159 reference statements)
1
13
0
2
Order By: Relevance
“…Next, we tested the ability of the CjDsbAs to introduce disulfide bonds in vitro using ribonuclease A (RNaseA) as its substrate; RNaseA needs four properly located disulfide bonds for its enzyme activity. The oxidative activity of the DsbAs was assessed by spectrophotometrically measuring the RNaseA cleavage of cCMP (cyclic-2′,3′cytidinemonophosphate) (Figure 1) [35,36]. We found that both CjDsbAs recognized RNaseA as their substrate and exhibited oxidase activity such as that of EcDsbA, in contrast to EcDsbL that, according to literature data, does not introduce disulfides into RNaseA [24].…”
Section: Biochemical and Functional Comparison Of Cjdsba1 And Cjdsba2mentioning
confidence: 54%
“…Next, we tested the ability of the CjDsbAs to introduce disulfide bonds in vitro using ribonuclease A (RNaseA) as its substrate; RNaseA needs four properly located disulfide bonds for its enzyme activity. The oxidative activity of the DsbAs was assessed by spectrophotometrically measuring the RNaseA cleavage of cCMP (cyclic-2′,3′cytidinemonophosphate) (Figure 1) [35,36]. We found that both CjDsbAs recognized RNaseA as their substrate and exhibited oxidase activity such as that of EcDsbA, in contrast to EcDsbL that, according to literature data, does not introduce disulfides into RNaseA [24].…”
Section: Biochemical and Functional Comparison Of Cjdsba1 And Cjdsba2mentioning
confidence: 54%
“…Disulfide bond formation is a crucial step in the folding process of a protein and is catalyzed by bacterial proteins of the Dsb system. DsbC is responsible for rearranging incorrect disulfides introduced between cysteine residues ( Banaś et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins vary widely. They can share as little as 7.37% identity with E. coli K‐12 DsbA (Banaś et al., 2020), sometimes, like DsbC, they form oligomers (Qin et al., 2009), and they can have either broad or narrow substrate specificities (Lin et al., 2009), all the while maintaining oxidase function. Moreover, fusions of DsbA with other proteins or protein domains often occur in prokaryotes.…”
Section: Engineering the Dsb System And Its Substratesmentioning
confidence: 99%